Evaluasi Kinerja Pengelolaan Obyek Wisata Pantai di DIY - Teguh Budi Prasetya; Endang Susilowati; Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2015)
With the potential is so great, Beach-Tourism can be regarded as a new future for the industrial tourism in  DIY. Character exotic beaches and not much exploited accompanied the opening of the South Cross Road Line (JJLS: Jalur Jalan Lintas Selatan) resulted Beach Tourism in this province has a very bright future. Development of beach tourism, especially in the karst area of Gunung Kidul will be a key growth area in the region's economy. The problem is, the management of existing beach-tourism destination is still so bad. Shore excursions still tend to be chaotic, expensive, dirty and aggravated expansion “asong-traders” to coastal areas that tend to interfere with the comfort of tourists. Finally, the beach resort far from friendly for tourists. This condition is believed, not to be separated from the failure of the management model in controlling the perpetrators of beach-tourism. This research generally want to formulate a model of partisipative management of beach-tourism on DIY and able to put into a beach- tourist travel featured DIY sector. In the first year (part I), research will evaluating against existing beach-tourist management model with the aim of getting information: Existing forms of institutional model and regulatory management of DIY beach tourism,strengths, weaknesses, opportunities and challenges faced, strategic issues of institutional development model of DIY beach tourism, At this stage of the research will be conducted evaluative and utilizing SWOT analysis to formulate a raw material for the development of the model.